2014
DOI: 10.1371/journal.pone.0104955
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin Is Expressed in the Mouse Uterus during Early Pregnancy and Promotes Mouse Blastocyst Attachment and Invasion In Vitro

Abstract: Embryo implantation into the maternal uterus is a decisive step for successful mammalian pregnancy. Osteopontin (OPN) is a member of the small integrin-binding ligand N-linked glycoprotein family and participates in cell adhesion and invasion. In this study, we showed that Opn mRNA levels are up-regulated in the mouse uterus on day 4 and at the implantation sites on days 5 and 8 of pregnancy. Immunohistochemistry localized the OPN protein to the glandular epithelium on day 4 and to the decidual zone on day 8 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 49 publications
(63 reference statements)
1
18
0
Order By: Relevance
“…Besides, previous studies also revealed OPN expression in stromal cells is increased at the end of the secretory phase, which is consistent with the time when perivascular stromal cells begin to decidualize (Apparao et al 2001, von Wolff et al 2004. OPN-deficient mice manifested a decreased pregnancy rate during mid-gestation and knockdown of OPN in mouse endometrial stromal cells lead to a restrained trophoblast invasion in vitro (Weintraub et al 2004, Qi et al 2014. Our previous study also proved that OPN is activated in mouse endometrial stromal cells (mESC) and human endometrial stromal cells (hESC) by estrogen (E2) and progesterone (P4) (von Wolff et al 2004, Qi et al 2014.…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…Besides, previous studies also revealed OPN expression in stromal cells is increased at the end of the secretory phase, which is consistent with the time when perivascular stromal cells begin to decidualize (Apparao et al 2001, von Wolff et al 2004. OPN-deficient mice manifested a decreased pregnancy rate during mid-gestation and knockdown of OPN in mouse endometrial stromal cells lead to a restrained trophoblast invasion in vitro (Weintraub et al 2004, Qi et al 2014. Our previous study also proved that OPN is activated in mouse endometrial stromal cells (mESC) and human endometrial stromal cells (hESC) by estrogen (E2) and progesterone (P4) (von Wolff et al 2004, Qi et al 2014.…”
Section: Introductionsupporting
confidence: 68%
“…OPN-deficient mice manifested a decreased pregnancy rate during mid-gestation and knockdown of OPN in mouse endometrial stromal cells lead to a restrained trophoblast invasion in vitro (Weintraub et al 2004, Qi et al 2014. Our previous study also proved that OPN is activated in mouse endometrial stromal cells (mESC) and human endometrial stromal cells (hESC) by estrogen (E2) and progesterone (P4) (von Wolff et al 2004, Qi et al 2014. These results suggested that OPN plays an important role in regulating blastocyst implantation and decidualization.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Reorganization of Îą3 integrin expression from the apico‐basal‐lateral surface of the LE to expression predominantly at the basal surface was induced by LIF. LIF treatment strongly induces expression of the RGD integrin‐binding ECM protein osteopontin (OPN), . Although OPN −/− mice and human erythroblasts exhibit defects in F‐actin filament organization, its apparent importance in embryo attachment is unclear as SPP1/OPN null mice do not exhibit implantation failure …”
Section: Leukaemia Inhibitory Factor In Embryo Implantationmentioning
confidence: 99%
“…This conclusion is based on the findings that FOXA2 expression is diminished in rescued glands, and that E2-rescued glands exhibit diminished expression of additional molecules (LIF, SPP1, Prss28, Prss29, Spink3, and Ttr) implicated in gland function. 46,47,[49][50][51][52][53][54] Thus, we concluded that kisspeptin/KISS1R signaling positively regulates both gland development and function.…”
Section: Uterine Kisspeptin and Kiss1r Regulate Endometrial Adenogenementioning
confidence: 71%